Farm management analysis in paddy granary areas in enhancing on-farm income - Terano, Rika; Mohamed, Zainal Abidin; Rezai, Golnaz (Faculty of Economics and Management, Czech University of Life Sciences Prague, 2013)
Income inequality between rural and urban areas is a persistent issue that has been frequently studied and discussed with the hope of introducing or improving schemes that would lead to closing the gap between these two areas. Traditionally, paddy farmers have been mired in poverty and their livelihood has largely relied on on-farm income. In rice granary areas, on-farm income has played an important role in providing rural livelihood among paddy farmer households. Since on-farm income has played an important role in the rural livelihood, it is important to comprehend the influential factors determining on-farm income of the paddy farmers and find solutions to improve their income level and enhance future agricultural developments on the main granaries. We attempt to find out confronting problems in relation to on-farm income in the paddy sector by concentrating on paddy granary areas in Kedah, Selangor and Terengganu. This paper tries to grasp the characteristics of farm management and reveal influential determinants of gross return per hectare in value term in the three paddy granary areas while computing the benefit-cost ratio. The sample farmers were interviewed to gather information on the individual farm management practices in each area and farm management analysis was employed to analyze the obtained information. The Cobb-Douglas production function was used to indicate the significant factors influencing the farmers’ income. The result shows that there are different characteristics of gross return from paddy in each studied granary area. The usage of pesticide, fertilizer and seedling method directly influence the gross return per hectare from paddy farming.